Assisting adaptation in a changing world - Webster, Michael M.; Twohey, Becky; Alagona, Peter S.; Arafeh-Dalmau, Nur; Colton, Madhavi A.; Eger, Aaron M.; Miller, Stephanie N.; Pecl, Gretta T.; Scheffers, Brett R.; Snyder, Rebecca (Frontiers in Environmental Science, 2023)
This is a provisional file, not the final typeset article Today, all ecosystems are undergoing environmental change due to human activity, and in many cases the rate of change is accelerating due to climate change. Consequently, conservation programs are increasingly focused on the response of organisms, populations, and ecosystems to novel conditions. In parallel, the field of conservation biology is developing and deploying new tools to assist adaptation, which we define as aiming to increase the probability that organisms, populations, and ecosystems successfully adapt to ongoing change in biotic and abiotic conditions. Practitioners are aiming to assist a suite of adaptive processes, including acclimatization, range shifts, and evolution at the individual and population level, while influencing the aggregate of these responses to assist ecosystem reorganization. The practice of assisting adaptation holds promise for environmental conservation, but effective policy and implementation will require thoughtful consideration of potential social and biological benefits and risks.